PENGARUH KEPERCAYAAN, MORAL DAN KEKUASAAN PEMERINTAH TERHADAP TINGKAT KEPATUHAN PAJAK DAN PENGGELAPAN PAJAK PADA KPP PRATAMA KEBON JERUK DUA - Wisnu Saputra Wisnu Saputra; Andi Andi (LPPM STIA Banten, 2016)
The purpose of this study is to develop and test the effect of Trust, Tax Morale and Power of Authorities towards the level of Tax Compliance and Tax Evasion. This study uses a slippery slope framework assumptions in determining the tax compliance which consists of two dimensions : Trust and Power of Authorities. However, to further develop the framework slippery slope this study adds one independent variable is tax morale. The respondents in this study is an individual taxpayers certain employers who are registered as taxpayers in KPP Kebon Jeruk Dua. Methods of data collection in this study used a questionnaire using convenience sampling technique that is distributed to respondents. Data analysis techniques in this study using a statistical test SPSS version 20.The results of this study revealed that the variable of Trust, Tax Morale and Power of Authorities has a positive and significant effect on the level of tax compliance. The variable of Trust, Tax Morale and Power of Authorities has a negative influence and significant to Tax Evasion.